Ontogenic variations in free and esterified fatty acids during somatic embryogenesis of flax (Linum usitatissimum L.) - Cunha, Ana (2003)
In vitro cultures of flax (Linum usitatissimum L.) were established on MS medium and four samplings were made during the 7 weeks of culture. The samples varied from the original hypocotyl segments (HS) at t0 and segments with incipient calli formation (HSC) after 2 weeks (t2), to embryogenic calli (EC), non-embryogenic calli (NEC) and somatic embryos (SE) collected after 5 (t5) and 7 weeks (t7). The respective free fatty acids (FFA) and esterified fatty acids (EFA) were extracted and analyzed, as methyl esters, by GC and GC-MS, and the data were submitted to ANOVA and PCA statistical analysis. The main FFA in all samples was 16:0, 18:0, 18:1, 18:2 and 18:3. EFA fractions were more diverse containing some less common FA. The development of SE was associated with a decrease in neutral lipids. Both the total FFA and the total EFA, as fractions of total lipids, increased with the dedifferentiation and the early calli formation leveling off thereafter (t5 to t7). FA variations related to dedifferentiation of hypocotyl tissues and growth of non-embryogenic calli, somatic embryogenesis, and development of somatic embryos were observed. Predominant or tissue-specific FA was also found. The value of 18:3/18:2 and 18:0/18:3 ratios as potential indicators of SE autotrophy and calli embryogenic capacity is discussed.